Indicadores de ciência e tecnologia para o monitoramento em biotecnologia e diagnóstico tecnológico: uma visão Institucional, normativa e de futuro - Freitas, José Erivaldo Bezerra de (2017)
Consolidated on the frontier of knowledge, modern biotechnology is seen as a strategic theme for the development of countries, one of the foundations of Economy. It is based on the development of products / processes / services of interest in many segments of the productive sector, prompting governments to search for strategies, action plans and incentive policies in this area. However, designing the best strategies depends on constant monitoring of scientific, technological and innovation development, a challenging task in ICTs in face of the enormous amount of information given by the information advances, and therefore, efficient tools are required to recover and analyze large data groups, contributing significantly to the process of discovery, and focusing only on the most relevant parts. The elaboration of indicators based on bibliographic data has contributed greatly to the analytical monitoring processes, providing great scientific, technological and social benefits, relevant details, and alerts on taking decisions. This work shows: (i) The elaboration and analysis of a set of bibliometric indicators on the scientific and technological production in Biotechnology, between 2001 and 2015; (ii) Analysis of bibliometric indicators of scientific and technological production at UFC, between 2000 and 2014, and Technological Diagnostics in CT-UFC. From the data recovery and analysis, indicators illustrated in the form of graphs were elaborated using specialized softwares (VantagePoint, Ucinet, NetDraw, GEPHI and Excel). The methodology included the use of INPI, Lattes Curriculum and Derwent Innovations Index (DII) databases. The set of bibliometric indicators of scientific production on Biotechnology was collected from Web of Science (articles, review articles, notes, letters) and Biotechnology periodics, and processed by VantagePoint; while bibliometric indicators of technological production on Biotechnology were obtained through DII and treated with the Earliest Priority Selector in accordance with OECD Patent Statistics Manual, and VantagePoint software for processing information and indicators. The main mechanism adopted for Technological Diagnosis was interviewing research groups registered in DGP-CNPq belonging to CT-UFC. Developed by NIT-UFSCar, the System of Diagnosis was used to consolidate the information as an inventory of identified developing technologies. The bibliometric results allowed the creation of strategies for scientific research, monitoring new lines of action, subsidizing the development of promising areas, contributing to decision making, identification of potentialities / fragilities, opportunities for action and challenges in the formation of S&T&I strategies